2009
DOI: 10.1158/0008-5472.can-08-3076
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Statin Attenuates the Cardiotoxicity of Doxorubicin in Mice

Abstract: Cardiotoxicity, which may result from intense cardiac oxidative stress and inflammation, is the main limiting factor of the anticancer therapy using doxorubicin. Because statins might exert beneficial pleiotropic cardiovascular effects, among other things, by anti-inflammatory and antioxidative mechanisms, we investigated whether or not fluvastatin pretreatment can attenuate doxorubicin-induced cardiotoxicity. Five days after a single injection of doxorubicin (20 mg/kg; i.p.), left ventricular (LV) function wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 36 publications
11
96
1
4
Order By: Relevance
“…DOX-induced increased superoxide/ROS generation is also an early event in vivo, as demonstrated by numerous studies (e.g., Refs. 6, 16, and 43), whereas more significant histological damage, cell death, and cardiac dysfunction peak only later (when DOX is no longer present in the circulation/myocardium), concomitantly with the increased myocardial NT formation (43,53,65) (Supplemental Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…DOX-induced increased superoxide/ROS generation is also an early event in vivo, as demonstrated by numerous studies (e.g., Refs. 6, 16, and 43), whereas more significant histological damage, cell death, and cardiac dysfunction peak only later (when DOX is no longer present in the circulation/myocardium), concomitantly with the increased myocardial NT formation (43,53,65) (Supplemental Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…37 Pretreatment with statins can attenuate doxorubicin-induced cardiotoxicity via anti-inflammatory effects. 38 Olson et al reported a novel anthracycline analog, DIDOX, which was structurally modified from doxorubicin. DIDOX inhibits the production of the pro-inflammatory cytokines, TNFα and IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effectiveness of these interventions, however, typically investigate only acute cardiotoxicity. [8][9][10][11] Such interventions targeted against acute cardiotoxicity include the use of iron chelators, 12 antioxidants, 13,14 statins, 15 and amino acid supplementation. 16,17 These acute DOX cardiotoxicity studies have limited clinical application, however, since chronic forms of DOX cardiotoxicity can 392577I CT10110.1177/153473541039257 7Hydock et alIntegrative Cancer Therapies 1 University of Northern Colorado, Greeley, CO, USA manifest in the absence of severe acute cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%